Ultrasensitive circular dichroism spectroscopy based on coupled quasi-bound states in the continuum - Guan Tingting; Wang Zhenyu; Wang Ruize; Wu Zihan; Wang Chaowei; Wu Dong; Chu Jiaru; Chen Yang (Nanophotonics)
Circular dichroism (CD) spectroscopy is essential for biochemistry, structural biology and pharmaceutical chemistry. While the chiroptical properties of chiral molecules are characterized by the Pasteur parameter κ, it is commonly conceived that the generation of CD is solely attributed to the imaginary part κ′′. However, since the imaginary part κ′′ is orders of magnitude smaller than the real part κ′ for most chiral molecules, the achievable sensitivity of CD spectroscopy is quite limited. Here, we report a recipe for realizing ultrasensitive CD spectroscopy based on the κ′ component of chiral molecules. Two quasi-bound states in the continuum are coupled by chiral molecules to form two hybridized branches, whose wavelengths and eigenpolarizations are very sensitive to the value of κ′. Giant CD signals over four orders of magnitude larger than the case without mode coupling are thus produced, paving the way towards chiral structure analysis at the single molecule level.